Occipital Intraparenchymal Myxopapillary Ependymoma: Case Report and Literature Review - Mewada, Tushit Bharat (Asian J Neurosurg, 2017)
Myxopapillary ependymoma (MPE) is a histological variant of ependymoma found in the conus medullaris or filum terminale region. Intracranial occurrence of the tumor is a rarity. The most characteristic histological feature of myxopapillary tumors is the abundance of intercellular and perivascular mucin and the arborizing vasculature, which tends to form papillae. We are reporting a 14-year-old patient presented with seizures caused by the right occipital region intraparenchymal lesion. Histopathology confirmed it to be MPE. Lesion was excised completely. Literature reviews on the topic are discussed regarding the histological findings, natural history, and outcome of surgically treated MPE. This is the fifth reported case of cerebral intraparenchymal primary MPE.